Optimized Energy Storage Integration for Enhancing Grid Stability under High Photovoltaic Penetration Scenarios - Kuo, Ming-Tse (Conference record of the Industry Applications Conference, 2025)
The integration of photovoltaic (PV) generation into electrical grids presents significant technical challenges due to its intermittent and unpredictable nature. With aggressive renewable energy targets, power system operators face increased risks to voltage stability, transient stability, and frequency stability. This paper analyzes the impact of large-scale PV integration on power system reliability and proposes optimized solutions involving battery energy storage systems (BESS). The study specifically investigates scenarios reflecting high PV penetration levels planned for 2025, simulating real-world disturbances including sudden PV outages, abrupt drops in PV power generation, and combined cycle generator outages under critical conditions. Comprehensive transient simulations conducted using industry-standard software reveal that without proper mitigation strategies, high PV penetration significantly degrades frequency stability, particularly during low-inertia scenarios in winter months. To address these issues, this research applies nonlinear multi-objective optimization techniques, utilizing the NSGA-II algorithm, to identify optimal configurations of energy storage capacities and operational strategies. The findings demonstrate that strategically sized and located BESS effectively enhance grid stability, minimize frequency excursions, and reduce the risk of load shedding. Compared to existing literature, this paper provides detailed operational insights, simulation-based evidence, and clear guidance for practically implementing energy storage solutions within high renewable penetration scenarios. The proposed methodology serves as a robust framework for utilities and grid operators aiming to reliably integrate renewable generation.